2020
DOI: 10.1080/19371918.2020.1808144
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anxiety Levels and Perceived Social Support during the Pandemic of COVID-19 in Turkey

Abstract: The uncertainty which is threatening and stressful prevents a person's perception of control and leads to maladaptive psychological reactions such as anxiety. We aimed to define the relationship between the state/ trait anxiety levels and perceived social support in the COVID-19 pandemic as a global crisis and stressor. Our main hypothesis was that perceived social support would negatively affect the levels of anxiety. A crosssectional community-based study was carried out using the relational screening model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 35 publications
7
89
0
7
Order By: Relevance
“…This indicates that living in a neighborhood with high social capital seems to be protective when it comes to maintaining wellbeing during times of crisis. Several studies from various countries have found protective effects from social support and social networks during the COVID-19 pandemic (e.g., Killgore et al, 2020;Özmete and Pak, 2020;Qi et al, 2020;Yu et al, 2020;Skalski et al, 2021). The findings in our study need to be interpreted carefully considering the threat of a selection bias.…”
Section: Discussionmentioning
confidence: 67%
“…This indicates that living in a neighborhood with high social capital seems to be protective when it comes to maintaining wellbeing during times of crisis. Several studies from various countries have found protective effects from social support and social networks during the COVID-19 pandemic (e.g., Killgore et al, 2020;Özmete and Pak, 2020;Qi et al, 2020;Yu et al, 2020;Skalski et al, 2021). The findings in our study need to be interpreted carefully considering the threat of a selection bias.…”
Section: Discussionmentioning
confidence: 67%
“…In the study conducted by Yağcı and Akfırat (2020), it was found that the traumatic stress levels experienced by individuals during the COVID-19 pandemic were below average, while the perceived social support levels were above average. In the studies conducted by Özmete and Pak (2020) during the COVID-19 pandemic, it was determined that the perceived social support levels were high, and the perceived social support from the family was higher than other dimensions. In another study by Bozdağ and Ergün (2020) on healthcare professionals, it was found that the perceived social support from family members was higher.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and social isolation caused by social distancing may cause individuals to lose their emotional ties with significant others, thereby leading to weaker social support [ 34 ]. Social support decreased anxiety levels during COVID-19 [ 35 ]. However, those living in foreign countries were likely living alone as well as at a considerable distance from their relatives and acquaintances, which heightened the likelihood of their experiencing psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%